Classroom learning and practical training experiences toward students’ career intentions in hospitality industry: a case in Politeknik Merlimau Melaka / Aylin Kamaruddin and Nor Ashikin Jamal - Kamaruddin, Aylin; Jamal, Nor Ashikin (Faculty of Hotel & Tourism Management, 2013)
Hospitality industry has become one of the preferred fields for students in pursuing a career. Inevitably, the role of hospitality educators, hospitality industry and student are interrelated. Therefore, the essential experiences in classroom or during their practical training can be considered as medium for students in changing their perceptions towards hospitality industry. Thus, an academician needs to be effective and creative in their teaching and learning in order to meet the preferences and the needs of the industry. Generally, students will gain interest based on their experience in determining their future career decision. The main purpose of this study was to determine if there was a relationship between classroom learning and practical training experience of students’ career intentions. Sample of 262 students in Hotel & Catering at Politeknik Merlimau Melaka were selected. This research analyzed the relationship of these dimensions and the intention to pursuing a career in hotel industry by the students. The most important dimension that influences the students’ intention also had been selected in the study. The results indicated positive relationships between both classroom learning dimensions and students’ career intention. Concisely, this research has shown the importance of understanding the best and appropriate choices of variable to encourage students in pursuing their career in hospitality industry.